Observing 0D subwavelength-localized modes at ~100 THz protected by weak topology - Lu, Jinlong; Wirth, Konstantin G.; Gao, Wenlong; Heßler, Andreas; Sain, Basudeb; Taubner, Thomas; Zentgraf, Thomas (Science Advances)
Topological photonic crystals (TPhCs) provide robust manipulation of light with built-in immunity to fabrication tolerances and disorder. Recently, it was shown that TPhCs based on weak topology with a dislocation inherit this robustness and further host topologically protected lower-dimensional localized modes. However, TPhCs with weak topology at optical frequencies have not been demonstrated so far. Here, we use scattering-type scanning near-field optical microscopy to verify mid-bandgap zero-dimensional light localization close to 100 THz in a TPhC with nontrivial Zak phase and an edge dislocation. We show that because of the weak topology, differently extended dislocation centers induce similarly strong light localization. The experimental results are supported by full-field simulations. Along with the underlying fundamental physics, our results lay a foundation for the application of TPhCs based on weak topology in active topological nanophotonics, and nonlinear and quantum optic integrated devices because of their strong and robust light localization.

Key Point Analysis via Contrastive Learning and Extractive Argument Summarization - Alshomary, Milad; Gurcke, Timon; Syed, Shahbaz; Heinisch, Philipp; Spliethöver, Maximilian; Cimiano, Philipp; Potthast, Martin; Wachsmuth, Henning (Proceedings of the 8th Workshop on Argument Mining)

iClarify - A Tool to Help Requesters Iteratively Improve Task Descriptions in Crowdsourcing - Nouri, Zahra; Prakash, Nikhil; Gadiraju, Ujwal; Wachsmuth, Henning (Proceedings of the Ninth AAAI Conference on Human Computation and Crowdsourcing, HCOMP 2021)

Near-Shortest Path Routing in Hybrid Communication Networks - Coy, Sam; Czumaj, Artur; Feldmann, Michael; Hinnenthal, Kristian; Kuhn, Fabian; Scheideler, Christian; Schneider, Philipp; Struijs, Martijn (25th International Conference on Principles of Distributed Systems, OPODIS 2021, December 13-15, 2021, Strasbourg, France)

Spring Forward, Don't Fall Back: The Effect of Daylight Saving Time on Road Safety - Bünnings, Christian; Schiele, Valentin (The Review of Economics and Statistics)
In this paper, we analyze the effect of light conditions on road accidents and estimate the long run consequences of different time regimes for road safety. Identification is based on variation in light conditions induced by differences in sunrise and sunset times across space and time. We estimate that darkness causes annual costs of more than £500 million in Great Britain. By setting daylight saving time year-round 8 percent of these costs could be saved. Thus, focusing solely on the short run costs related to the transition itself underestimates the total costs of the current time regime.

Online Monitoring des Beschichtungsprozesses im Laser Sintern, Systementwicklung und Einflussanalyse - Klippstein, Sven Helge

Influences of Temperature-Dependent Boundary Conditions on Component Properties in Arburg Plastic Freeforming - Moritzer, Elmar; Hecker, Felix; Elsner, Christian Lennart; Hirsch, André (Proceedings of 36th Annual Meeting of Polymer Processing Society (PPS-36))

Comparison of unidirectional Three- and Four-Wire based Boost PFC-Rectifier Topologies for Non-Isolated Three-Phase EV On-Board Chargers under Common-Mode Aspects - Hagemeyer, Marc; Wallmeier, Peter; Schafmeister, Frank; Böcker, Joachim (Proc. 36th IEEE Applied Power Electronics Conference (APEC))

Transformerless On-Board Chargers at Three- and Single-Phase Operation: Compensation of LF Common-Mode Noise by the Internal DC/DC-Stage - Schafmeister, Frank (Power System Design (PSD) Web Magazine)

Influence of household regeneration techniques on the filtration efficiency of FFP2 and surgical masks in the submicron size range - Tischendorf, Ricardo; Schmid, Hans-Joachim

Influence of Atomization on Particle Formation in Spray Flames - Tischendorf, Ricardo; Schmid, Hans-Joachim; Bieber, M.; Reddemann, M.; Kneer, R.; Fröde, F.; Grenga, T.; Pitsch, H.

Einfluss der Zerstäubung auf die Partikelsynthese in Sprayflammen - Tischendorf, Ricardo; Schmid, Hans-Joachim; Bieber, M.; Reddemann, M.; Kneer, R.; Fröde, F.; Grenga, T.; Pitsch, H.

Simplifying Robot Programming using Augmented Reality and End-User Development - Yigitbas, Enes; Jovanovikj, Ivan; Engels, Gregor (Proceedings of the 18th IFIP TC13 International Conference on Human-Computer Interaction (INTERACT 2021))

Using Augmented Reality for Enhancing Planning and Measurements in the Scaffolding Business - Yigitbas, Enes; Sauer, Stefan; Engels, Gregor (Proceedings of the 13th ACM SIGCHI Symposium on Engineering Interactive Computing Systems (EICS 2021))

Collaborative Software Modeling in Virtual Reality - Yigitbas, Enes; Gorissen, Simon; Weidmann, Nils; Engels, Gregor (Proceedings of the 24th International Conference on Model Driven Engineering Languages and Systems (MODELS'21))

Lossless, Persisted Summarization of Static Callgraph, Points-To and Data-Flow Analysis - Schubert, Philipp; Hermann, Ben; Bodden, Eric (European Conference on Object-Oriented Programming (ECOOP))
Static analysis is used to automatically detect bugs and security breaches, and aids compileroptimization. Whole-program analysis (WPA) can yield high precision, however causes long analysistimes and thus does not match common software-development workflows, making it often impracticalto use for large, real-world applications.This paper thus presents the design and implementation ofModAlyzer, a novel static-analysisapproach that aims at accelerating whole-program analysis by making the analysis modular andcompositional. It shows how to computelossless, persisted summaries for callgraph, points-to anddata-flow information, and it reports under which circumstances this function-level compositionalanalysis outperforms WPA.We implementedModAlyzeras an extension to LLVM and PhASAR, and applied it to 12 real-world C and C++ applications. At analysis time,ModAlyzermodularly and losslessly summarizesthe analysis effect of the library code those applications share, hence avoiding its repeated re-analysis.The experimental results show that the reuse of these summaries can save, on average, 72% ofanalysis time over WPA. Moreover, because it is lossless, the module-wise analysis fully retainsprecision and recall. Surprisingly, as our results show, it sometimes even yields precision superior toWPA. The initial summary generation, on average, takes about 3.67 times as long as WPA.

Measurement and modelling solubility of amino acids and peptides in aqueous 2-propanol solutions - Do, Hoang Tam; Franke, Patrick; Volpert, Sophia; Klinksiek, Marcel; Thome, Max; Held, Christoph (Physical Chemistry Chemical Physics)
In this work the solubility of 15 amino acids and 18 peptides in aqueous 2-propanol solutions was successfully modelled using PC-SAFT that used recently determined experimental melting properties as input data.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Modeling and investigations of chemical absorption process for prevention of emergencies - Bothe, Mike; Fedorov, Alexander; Frei, Herrmann; Kenig, Eugeny

Inverse parameter identification of an anisotropic plasticity model for sheet metal - Friedlein, J.; Wituschek, S.; Lechner, M.; Mergheim, J.; Steinmann, P. (IOP Conference Series: Materials Science and Engineering)
The increasing economic and ecological demands on the mobility sector require efforts to reduce resource consumption in both the production and utilization phases. The use of lightweight construction technologies can save material and increase energy efficiency during operation. Multi-material systems consisting of different materials and geometries are used to achieve weight reduction. Since conventional joining processes reach their limits in the connection of these components, new methods and technologies are necessary in order to be able to react versatilely to varying process and disturbance variables. For fundamental investigations of new possibilities in joining technology, numerical investigations are helpful to identify process parameters. To generate valid results, robust and efficient material models are developed which are adapted to the requirements of versatile joining technologies, for instance to the high plastic strains associated with self-piercing riveting. To describe the inherent strain-induced plastic orthotropy of sheet metal an anisotropic Hill-plasticity model is formulated. Tensile tests for different sheet orientations are conducted both experimentally and numerically to adjust the anisotropic material parameters by inverse parameter identification for aluminium EN AW-6014 and steel HCT590X. Then, the layer compression test is used to validate the model and the previously identified parameters.

Energy direction in ultrasonic impregnation of continuous fiber-reinforced thermoplastics - Popp, J.; Wolf, M.; Mattner, T.; Drummer, D. (Journal of Composites Science)
As a new and innovative processing method for fabrication for fiber-reinforced thermoplastic composites (CFRTs), the feasibility of ultrasonic welding technology was proven in several studies. This method offers potential for the direct manufacturing of CFRT–metal structures via embedded pin structures. Despite the previous studies, a deeper understanding of the process of energy input and whether fibers work as energy directors and consequently can, in combination with chosen processing parameters, influence the consolidation quality of the CFRTs, is still unknown. Consequently, the aim of this work is to establish a deeper process understanding of the ultrasonic direct impregnation of fiber-reinforced thermoplastics with an emphasis on the fiber’s function as energy directors. Based on the generated insights, a better assessment of the feasibility of direct, hybrid part manufacturing is possible. The produced samples were primarily evaluated by optical and mechanical test methods. It is demonstrated that with higher welding time and amplitude, a better consolidation quality can be achieved and that independent of the process parameters chosen in this study, no significant fiber breakage occurs. This is interpreted as a sign of a gentle impregnation process. Furthermore, based on the examination of single roving and 5-layer set-ups, it is shown that the glass fibers function as energy directors and can influence the transformation of sonic energy into thermal energy. In comparison to industrially available CFRT material, the mechanical properties are weaker, but materials and processes offer potential for significant improvement. Based on these findings, proposals for a direct impregnation and joining process are made.

Influence of the production process on the binding mechanism of clinched aluminum steel mixed compounds - Kalich, J.; Füssel, U. (Journal of Manufacturing and Materials Processing)
The multi-material design and the adaptability of a modern process chain require joining connections with specifically adjustable mechanical, thermal, chemical, or electrical properties. Previous considerations primarily focused on the mechanical properties. The multitude of possible combinations of requirements, materials, and component- and joining-geometry makes an empirical determination of these joining properties for the clinching process impossible. Based on the established and empirical procedure, there is currently no model that takes into account all questions of joinability—i.e., the materials (suitability for joining), design (security of joining), and production (joining possibility)—that allows a calculation of the properties that can be achieved. It is therefore necessary to describe the physical properties of the joint as a function of the three binding mechanisms—form closure, force closure, and material closure—in relation to the application. This approach illustrates the relationships along the causal chain “joint requirement-binding mechanism-joining parameters” and improves the adaptability of the mechanical joining technology. Geometrical properties of clinch connections of the combination of aluminum and steel are compared in a metallographic cross-section. The mechanical stress state of the rotationally symmetrical clinch points is qualified with a torsion test and by measuring the electrical resistance in the base material, in the clinch joint, and during the production cycle (after clinching, before precipitation hardening and after precipitation hardening).

Stochastic local FEM for computational homogenization of heterogeneous materials exhibiting large plastic deformations - Pivovarov, D.; Mergheim, J.; Willner, K.; Steinmann, P. (Computational Mechanics)
Computational homogenization is a powerful tool allowing to obtain homogenized properties of materials on the macroscale from simulations of the underlying microstructure. The response of the microstructure is, however, strongly affected by variations in the microstructure geometry. In particular, we consider heterogeneous materials with randomly distributed non-overlapping inclusions, which radii are also random. In this work we extend the earlier proposed non-deterministic computational homogenization framework to plastic materials, thereby increasing the model versatility and overall realism. We apply novel soft periodic boundary conditions and estimate their effect in case of non-periodic material microstructures. We study macroscopic plasticity signatures like the macroscopic von-Mises stress and make useful conclusions for further constitutive modeling. Simulations demonstrate the effect of the novel boundary conditions, which significantly differ from the standard periodic boundary conditions, and the large influence of parameter variations and hence the importance of the stochastic modeling.

Anisotropic plasticity‐damage material model for sheet metal — Regularised single surface formulation - Friedlein, J.; Mergheim, J.; Steinmann, P. (PAMM)
Sheet metal forming as well as mechanical joining demand increasingly accurate and efficient material modelling to capture large deformations, the inherent sheet orthotropy and even process-induced damage, which is expected to be influential. To account for large strains the additive logarithmic strain space is utilised that enables a straightforward incorporation of plastic anisotropy, herein modelled by a Hill48 yield function. A gradient-enhancement is used to equip the ductile damage model with an internal length scale curing the damage-induced localisation. An affine combination of the local and non-local softening variable is derived enabling a more efficient single surface formulation for the regularised plasticity-damage material model.

Further development of a numerical method for analyzing the load capacity of clinched joints in versatile process chains - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson

Data-driven analysis of cold-formed pin structure characteristics in the context of versatile joining processes - Römisch, D.; Zirngibl, C.; Schleich, B.; Wartzack, S.; Merklein, M. (IOP Conference Series: Materials Science and Engineering)
Due to increasingly strict emission targets and regulatory requirements, especially for companies in the transport industry, the demand for multi-material-systems is continuously rising in order to lower energy consumption. In this context, mechanical joining processes offer an environmentally friendly and flexible alternative to established joining methods, especially in the field of lightweight design. For example, cold-formed cylindrical pin structures show high potentials in joining multi-material-systems without auxiliary elements. The pin structures are joined either by pressing them directly into the joining partner or by caulking with a pre-punched part. However, to evaluate the strength of the joint and to ensure the joining reliability for versatile processes, such as changing joining partners or batch variations, engineering designers currently have only limited design principles available compared to thermal joining processes. Consequently, the design of an optimal pin joint requires cost- and time-intensive experimental investigations and adjustments to design or process parameters. As a solution, data-driven methods offer procedures for structuring data and identifying dependencies between varying process parameters and resulting pin structure characteristics. Motivated by this, the paper presents an approach for the data-driven analysis of cold-formed pin structures and offers a deeper understanding of how versatile processes affect the pin characteristics. Therefore, the application of an intelligent design of experiment in combination with several machine learning methods enable the setup of a best-fitting meta-model. Resulting, the determination of a mathematical model provides the opportunity to accurately estimate the pin height considering only relevant geometrical and process parameters with a prediction quality of 95 %.

Numerical and experimental investigation of the transmission moment of clinching points - Steinfelder, C.; Kalich, J.; Brosius, A.; Füssel, U. (IOP Conference Series: Materials Science and Engineering)
In clinching, the combinations of requirements, materials, component dimensions and tools influence the resulting joint geometry and the resulting bonding mechanisms. These in turn affect the property profile of the joint. For example, it is possible to use different tools to flexibly adapt clinching points to the respective required load regime. Clinching points dimensioned in this way can be geometrically similar, but have different mechanical stress states, which leads to different properties in terms of load-bearing behavior. Within the scope of this work, the clinching process with different tools in optimal and compromise design and its effect on the force and form-closure component, is investigated in a torsion test of the clinched connection. Clinched steel sheets with two thicknesses and joining directions are analyzed. Virtual experiments are carried out using finite element analyses (FEA) of the joining process and are followed by a springback simulation. Subsequently, the surface pressure between the two joining partners in the clinching points is calculated on the basis of the results from the FEA and the transmittable moment of the connection, as an indicator for the force-closure component, is determined. Finally, the experimental and simulated data are compared and discussed.

Fiber Orientation Mechanism of Continuous Fiber Reinforced Thermoplastics Hybrid Parts Joined with Metallic Pins - Popp, J.; Kleffel, T.; Römisch, D.; Papke, T.; Merklein, M.; Drummer, D. (Applied Composite Materials)
Continuous Fiber Reinforced Thermoplastic (CFRT) hybrid parts offer interesting possibilities for lightweight application, which can exceed the capabilities of mono material metal or CFRT parts. In this case, the joining technology oftentimes is the limiting factor. This study investigates a joining operation with metal pin structures which are additively manufactured via powder bed fusion featuring different diameters and tip geometries, which are inserted into the locally infrared heated CFRT part. The resulting fiber rearrangement is assessed using transmitted light microscopy, confocal laser scanning microscopy as well as micro-computer-tomography. It could be shown that for all assessed pin variants a similar distinct fiber displacement can be seen and that the pin diameter has a significant effect on the resulting fiber orientation with smaller pin diameters being advantageous because of gentle fiber displacement and reduced undulation. The tip geometry has only minor effect on the fiber orientation. Especially in the X/Y plane no systematic influence of the tip geometry on the fiber displacement could be observed. Based on the gained insights a three-stage model of the fiber orientation processes is proposed.

Clinching of Thermoplastic Composites and Metals—A Comparison of Three Novel Joining Technologies - Gröger, B.; Troschitz, J.; Vorderbrüggen, J.; Vogel, C.; Kupfer, R.; Meschut, G.; Gude, M. (Materials)
Clinching continuous fibre reinforced thermoplastic composites and metals is challenging due to the low ductility of the composite material. Therefore, a number of novel clinching technologies has been developed specifically for these material combinations. A systematic overview of these advanced clinching methods is given in the present paper. With a focus on process design, three selected clinching methods suitable for different joining tasks are described in detail. The clinching processes including equipment and tools, observed process phenomena and the resultant material structure are compared. Process phenomena during joining are explained in general and compared using computed tomography and micrograph images for each process. In addition the load bearing behaviour and the corresponding failure mechanisms are investigated by means of single-lap shear tests. Finally, the new joining technologies are discussed regarding application relevant criteria.

Determination of the Interface Structural Resolution of an Industrial X-Ray Computed Tomograph Using a Spherical Specimen and a Gap Specimen Consisting of Gauge Blocks - Busch, M.; Hausotte, T. (Key Engineering Materials)
Industrial X-ray computed tomography (XCT) is a tool for non-destructive testing and a volumetric analysis method with the ability to measure dimensions and geometry inside a component without destroying it. However, XCT is a relatively young technology in the field of dimensional metrology and thus faces several challenges. The achievement of a high measurement resolution, which is re-quired to detect small geometrical features, depends on a variety of influencing factors. In this arti-cle, the interface structural resolution (ISR) as one of the key challenges will be investigated. The two-sphere standard called the hourglass standard allows the determination of the structural resolu-tion by evaluation of the surrounding area of an ideal point contact of two spheres after the CT re-construction in form of a neck-shaped transition. Close to the contact point of the two spheres two opposing surfaces exist. Their distances from each other increase as the distance from the contact point of the two spheres increase. The determination of the distances between the spheres’ surface allows a statement about the ISR. A new developed specimen or standard with a variable gap size consisting of calibrated parallel gauge blocks allows statements about the ISR, too. Because of the higher number of probing points of the gauge block standard the results of the determined ISR are more stable compared to the hourglass standard. This paper compares the results of the computed tomography measurements for the designed interface structural resolution standard with those of the hourglass standard.

Testification of Condorcet Winners in dueling bandits - Haddenhorst, Björn; Bengs, Viktor; Brandt, Jasmin; Hüllermeier, Eyke (Proceedings of the Thirty-Seventh Conference on Uncertainty in Artificial Intelligence)
Several algorithms for finding the best arm in the dueling bandits setting assume the existence of a Condorcet winner (CW), that is, an arm that uniformly dominates all other arms. Yet, by simply relying on this assumption but not verifying it, such algorithms may produce doubtful results in cases where it actually fails to hold. Even worse, the problem may not be noticed, and an alleged CW still be produced. In this paper, we therefore address the problem as a ”testification” task, by which we mean a combination of testing and identification: The online identification of the CW is combined with the statistical testing of the CW assumption. Thus, instead of returning a supposed CW at some point, the learner has the possibility to stop sampling and refuse an answer in case it feels confident that the CW assumption is violated. Analyzing the testification problem formally, we derive lower bounds on the expected sample complexity of any online algorithm solving it. Moreover, a concrete algorithm is proposed, which achieves the optimal sample complexity up to logarithmic terms.

Clinching in In-situ CT – Experimental Study on Suitable Tool Materials - Köhler, D.; Kupfer, R.; Troschitz, J.; Gude, M. (ESAFORM 2021)
In lightweight design, clinching is a cost-efficient solution as the joint is created through localized cold-forming of the joining parts. A clinch point’s quality is usually assessed using ex-situ destructive testing methods. These, however, are unable to detect phenomena immediately during the joining process. For instance, elastic deformations reverse and cracks close after unloading. In-situ methods such as the force-displacement evaluation are used to control a clinching process, though deviations in the clinch point geometry cannot be derived with this method. To overcome these limitations, the clinching process can be investigated using in-situ computed tomography (in-situ CT). However, a clinching tool made of steel would cause strong artefacts and a high attenuation in the CT measurement, reducing the significance of this method. Additionally, when joining parts of the same material, the sheet-sheet interface is hardly detectable. This work aims at identifying, firstly, tool materials that allow artefact-reduced CT measurements during clinching, and, secondly, radiopaque materials that can be applied between the joining parts to enhance the detectability of the sheet-sheet interface. Therefore, both CT-suitable tool materials and radiopaque materials are selected and experimentally investigated. In the clinching process, two aluminium sheets with radiopaque material in between are clinched in a single-step (rotationally symmetric joint without cut section). It is shown that e.g. silicon nitride is suited as tool material and a tin layer is suitable to enhance the detectability of the sheet-sheet interface.

In Situ Computed Tomography—Analysis of a Single-Lap Shear Test with Clinch Points - Köhler, D.; Kupfer, R.; Troschitz, J.; Gude, M. (Materials)
As lightweight design gains more and more attention, time and cost-efficient joining methods such as clinching are becoming more popular. A clinch point’s quality is usually determined by ex situ destructive analyses such as microsectioning. However, these methods do not yield the detection of phenomena occurring during loading such as elastic deformations and cracks that close after unloading. Alternatively, in situ computed tomography (in situ CT) can be used to investigate the loading process of clinch points. In this paper, a method for in situ CT analysis of a single-lap shear test with clinched metal sheets is presented at the example of a clinched joint with two 2 mm thick aluminum sheets. Furthermore, the potential of this method to validate numerical simulations is shown. Since the sheets’ surfaces are locally in contact with each other, the interface between both aluminum sheets and therefore the exact contour of the joining partners is difficult to identify in CT analyses. To compensate for this, the application of copper varnish between the sheets is investigated. The best in situ CT results are achieved with both sheets treated. It showed that with this treatment, in situ CT is suitable to properly observe the three-dimensional deformation behavior and to identify the failure modes.

Friction Characterisation for a Tumbling Self-Piercing Riveting Process - Wituschek, S.; Lechner, M. (Key Engineering Materials)
Due to increasing demands regarding ecological and economic specifications in vehicle design, the effort required for production is continuously increasing. One trend is the increased use of multi-material systems, which are characterised by the use of different materials such as high-strength steels or aluminium alloys. In addition to the varying mechanical properties of the components, an increased number of variants accompanied by different geometries is leading to increasing challenges on body construction. For the assembly and connection of the individual components, conventional joining methods reach their limitations. Therefore, new joining methods are necessary, which feature properties of versatility and can adapt to process and disturbance variables. One way of achieving tailored joints is to use a tumbling self-piercing riveting process. For the design of the process route, numerical investigations are necessary for which a characterisation of the friction properties is necessary. This paper therefore investigates the contact and friction conditions that occur in a tumbling self-piercing riveting process. The individual contacts between the process components are identified and based on this, suitable processes for the characterisation of the friction factors - and coefficients are selected and performed.

Identification of the Generalized Condorcet Winner in Multi-dueling Bandits - Haddenhorst, Björn; Bengs, Viktor; Hüllermeier, Eyke (Advances in Neural Information Processing Systems)

Technikphilosophie - Peckhaus, Volker (Staatslexikon. Recht, Wirtschaft, Gesellschaft, Bd. 5: Schule - Virtuelle Realität)

Practical sufficient conditions for convergence of distributed optimisation algorithms over communication networks with interference - Redder, Adrian; Ramaswamy, Arunselvan; Karl, Holger (arXiv:2105.04230)
Information exchange over networks can be affected by various forms of delay. This causes challenges for using the network by a multi-agent system to solve a distributed optimisation problem. Distributed optimisation schemes, however, typically do not assume network models that are representative for real-world communication networks, since communication links are most of the time abstracted as lossless. Our objective is therefore to formulate a representative network model and provide practically verifiable network conditions that ensure convergence of distributed algorithms in the presence of interference and possibly unbounded delay. Our network is modelled by a sequence of directed-graphs, where to each network link we associate a process for the instantaneous signal-to-interference-plus-noise ratio. We then formulate practical conditions that can be verified locally and show that the age of information (AoI) associated with data communicated over the network is in $\mathcal{O}(\sqrt{n})$. Under these conditions we show that a penalty-based gradient descent algorithm can be used to solve a rich class of stochastic, constrained, distributed optimisation problems. The strength of our result lies in the bridge between practical verifiable network conditions and an abstract optimisation theory. We illustrate numerically that our algorithm converges in an extreme scenario where the average AoI diverges.

Ranking Structured Objects with Graph Neural Networks - Damke, Clemens; Hüllermeier, Eyke (Proceedings of The 24th International Conference on Discovery Science (DS 2021))
Graph neural networks (GNNs) have been successfully applied in many structured data domains, with applications ranging from molecular property prediction to the analysis of social networks. Motivated by the broad applicability of GNNs, we propose the family of so-called RankGNNs, a combination of neural Learning to Rank (LtR) methods and GNNs. RankGNNs are trained with a set of pair-wise preferences between graphs, suggesting that one of them is preferred over the other. One practical application of this problem is drug screening, where an expert wants to find the most promising molecules in a large collection of drug candidates. We empirically demonstrate that our proposed pair-wise RankGNN approach either significantly outperforms or at least matches the ranking performance of the naive point-wise baseline approach, in which the LtR problem is solved via GNN-based graph regression.
Keywords: Graph-structured data; Graph neural networks; Preference learning; Learning to rank

Towards Green Automated Machine Learning: Status Quo and Future Directions - Tornede, Tanja; Tornede, Alexander; Hanselle, Jonas Manuel; Wever, Marcel Dominik; Mohr, Felix; Hüllermeier, Eyke (arXiv:2111.05850)
Automated machine learning (AutoML) strives for the automatic configuration of machine learning algorithms and their composition into an overall (software) solution - a machine learning pipeline - tailored to the learning task (dataset) at hand. Over the last decade, AutoML has developed into an independent research field with hundreds of contributions. While AutoML offers many prospects, it is also known to be quite resource-intensive, which is one of its major points of criticism. The primary cause for a high resource consumption is that many approaches rely on the (costly) evaluation of many machine learning pipelines while searching for good candidates. This problem is amplified in the context of research on AutoML methods, due to large scale experiments conducted with many datasets and approaches, each of them being run with several repetitions to rule out random effects. In the spirit of recent work on Green AI, this paper is written in an attempt to raise the awareness of AutoML researchers for the problem and to elaborate on possible remedies. To this end, we identify four categories of actions the community may take towards more sustainable research on AutoML, i.e. Green AutoML: design of AutoML systems, benchmarking, transparency and research incentives.

A PLIC-based method for species mass transfer at free fluid interfaces - Schulz, Andreas; Wecker, Christian; Inguva, Venkatesh; Lopatin, Alexey S.; Kenig, Eugeny Y. (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Automated Machine Learning for Multi-Label Classification - Wever, Marcel Dominik

Immersive augmented reality system for the training of pattern classification control with a myoelectric prosthesis - Boschmann, Alexander; Neuhaus, Dorothee; Vogt, Sarah; Kaltschmidt, Christian; Platzner, Marco; Dosen, Strahinja (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Hand amputation can have a truly debilitating impact on the life of the affected person. A multifunctional myoelectric prosthesis controlled using pattern classification can be used to restore some of the lost motor abilities. However, learning to control an advanced prosthesis can be a challenging task, but virtual and augmented reality (AR) provide means to create an engaging and motivating training. Methods In this study, we present a novel training framework that integrates virtual elements within a real scene (AR) while allowing the view from the first-person perspective. The framework was evaluated in 13 able-bodied subjects and a limb-deficient person divided into intervention (IG) and control (CG) groups. The IG received training by performing simulated clothespin task and both groups conducted a pre- and posttest with a real prosthesis. When training with the AR, the subjects received visual feedback on the generated grasping force. The main outcome measure was the number of pins that were successfully transferred within 20 min (task duration), while the number of dropped and broken pins were also registered. The participants were asked to score the difficulty of the real task (posttest), fun-factor and motivation, as well as the utility of the feedback. Results The performance (median/interquartile range) consistently increased during the training sessions (4/3 to 22/4). While the results were similar for the two groups in the pretest, the performance improved in the posttest only in IG. In addition, the subjects in IG transferred significantly more pins (28/10.5 versus 14.5/11), and dropped (1/2.5 versus 3.5/2) and broke (5/3.8 versus 14.5/9) significantly fewer pins in the posttest compared to CG. The participants in IG assigned (mean ± std) significantly lower scores to the difficulty compared to CG (5.2 ± 1.9 versus 7.1 ± 0.9), and they highly rated the fun factor (8.7 ± 1.3) and usefulness of feedback (8.5 ± 1.7). Conclusion The results demonstrated that the proposed AR system allows for the transfer of skills from the simulated to the real task while providing a positive user experience. The present study demonstrates the effectiveness and flexibility of the proposed AR framework. Importantly, the developed system is open source and available for download and further development.
Keywords: Health Informatics; Rehabilitation

Exploiting Hardware-Based Data-Parallel and Multithreading Models for Smart Edge Computing in Reconfigurable FPGAs - Rodriguez, Alfonso; Otero, Andres; Platzner, Marco; De la Torre, Eduardo (IEEE Transactions on Computers)
Keywords: Computational Theory and Mathematics; Hardware and Architecture; Theoretical Computer Science; Software

Injection Molding of Wood-Filled Thermoplastic Polyurethane - Moritzer, Elmar; Richters, Maximilian (Journal of Composites Science)
Wood fiber reinforcement of plastics is almost limited to polypropylene, polyethylene, polyvinyl chloride and polystyrene. Wood fiber reinforcement of thermoplastic polyurethanes (TPU) is a new research field and paltry studied scientifically. Wood fiber reinforcement can carry out synergistic effects between sustainability, material or product price reduction, improved mechanical properties at high elongation, and brilliant appearance and haptics. In order to evaluate to what extent the improvement of mechanical properties depend on material-specific parameters (fiber type, fiber content) and on process-specific parameters (holding pressure, temperature control and injection speed), differently filled compounds were injection molded according to a partial factorial test plan and subjected to characterizing test procedures (tensile test, Shore hardness and notched impact test). Tensile strength showed significant dependence on barrel temperature, fiber type and interaction between holding pressure and barrel temperature in the region of interest. Young’s modulus can be influenced by fiber content but not by fiber type. Notched impact strength showed a significant influence of cylinder temperature, fiber content, fiber type and the interaction between cylinder temperature and fiber content in the region of interest. Shore hardness is related to fiber content and the interaction between mold temperature and injection flow rate. Our results show not only that wood-filled TPU can be processed very well by injection molding, but also that the mechanical properties depend significantly on temperature control in the injection-molding process. Moreover, considering the significant reinforcing effect of the wood fibers, a good fiber-matrix adhesion can be assumed.
Keywords: Engineering (miscellaneous); Ceramics and Composites

Characterization of wood-filled thermoplastic polyurethane for the injection modling process - Moritzer, Elmar; Richters, Maximilian (Journal of Applied Polymer Science)

Mit dem Schraubblind-Durchsetznieten Metallteile mit Composites bei einseitiger Zugänglichkeit verbinden - Moritzer, Elmar; Richters, Maximilian; Hillemeyer, Johannes; Krassmann, Dimitri (Joining Plastics)

Florian braucht Mehmet mehr als umgekehrt: Herausforderungen und Potenziale für Inklusion in der Freiwilligen Feuerwehr - Kastein, Mara; Finke, Josefine; Horwath, Ilona (Voluntaris)

Ohne den ‚Weissen Mann‘ würden Leute wie Sie noch in Erdhöhlen wohnen.“ - Die Markierung der Unmarkierten (Erscheinungsformen, Erklärungsversuche und Gegenstrategien, GENDER)

Feuerwehren im Spiegel gesellschaftlicher Diversität - Horwath, Ilona; Kastein, Mara; Duglar Sezer, Nilgün (Feuerwehren im Spiegel gesellschaftlicher Diversität)

Das schwankende Schiff der Männerpolitik: eine Metaphernanalyse - Kastein, Mara (Forum Qualitative Sozialforschung)
In dem Artikel werden die Metaphern gleichstellungsorientierter Männerpolitik als eine Form diskursiver Praktiken untersucht. In meiner Dissertation habe ich die Metaphernanalyse ergänzend zur Grounded-Theory-Methodologie und zur wissenssoziologischen Diskursanalyse genutzt, um die Ergebnisse zu verdichten und zu vertiefen. Dabei stellt die Metaphorik der gleichstellungsorientierten Männerpolitik selbige als instabil, schwankend, balancierend und uneinig dar, denn sie wird als schwankendes Schiff, welches ohne feste Route auf dem Meer schaukelt, imaginiert. Das Meer ist die Gesellschaft bzw. die übergeordnete Gleichstellungspolitik. Diese wird als unberechenbar und launisch konzipiert, und die gleichstellungsorientierte Männerpolitik erscheint dabei als ausgeliefert.

International Perspectives about COVID-19, Digital Labour and Gender Work Pattern: A Collective Interview (Gender a výzkum / Gender and Research)

A Plea to Reflect on the Entanglements of Gendered Work Patterns and Digital Technologies (Gender a výzkum / Gender and Research)

The influence of manufacturing processes and optical measurement methods on the damage behavior of HX340LAD micro-alloyed steels - Otroshi, Mortaza; Meschut, Gerson; Nesakumar, Aathavan (Journal of Manufacturing Engineering)
This study deals with the damage behavior of metallic materials by the application of different manufacturing processes and using different optical measurement methods to identify the crack initiation in the damage specimen. The study is intended to highlight the importance of considering manufacturing processes and optical measurement methods in a numerical simulation when analyzing the damage behavior of metallic materials. To describe the damage behavior of the material in the process chain simulations, it is important to calibrate the parameters of damage model more accurately. These parameters are determined using experimental investigation of desired damage specimens. In this regard, a selected damage specimen manufactured by different cutting processes is first experimentally and then numerically investigated. It is shown that the manufacturing process and the optical measurement methods influence the stress state analyzed in the numerical simulation.
Keywords: Damage behaviour; Stress triaxiality; Manufacturing process and Optical measurement

Investigation of Plastic Freeformed, Open-Pored Structures with Regard to Producibility, Reproducibility and Liquid Permeability - Moritzer, Elmar; Hirsch, André; Dalmer, C.
The Arburg Plastic Freeforming (APF) is an additive manufacturing process which allows the production of three-dimensional thermoplastic components in layers. The components are produced by depositing fine, molten plastic droplets. The main advantage of the APF is the open-parameter control of the associated machine system. Thus, the process parameters can be optimized for individual applications. A special and new application of the APF is the production of interconnecting porous structures. As this is a novel approach with this manufacturing process, the general producibility and reproducibility must first be proven. Therefore, the relevant process parameters with an influence on the open-pored structures are identified. The volume of the individual plastic droplets, the distance between the droplets and the layer thickness are the three decisive influencing factors. With the use of analysis methods, the free spaces created in the structure are described by a uniformly constructed, interconnected pore structure. This means that the pores are interconnected in three dimensions. Reproducibility is evaluated by repeated production and thru the changed conditions during the manufacturing process. In addition, the multiplication and a change of geometry are evaluated in such a way that there is no influence on the pore size. Irregularities when depositing the first layer are caused by unevenness of the building platform. A suitable test arrangement is set up to determine the liquid permeability. A characteristic value is determined to describe the permeability to liquids.

Investigation of Specific FDM Process Parameters to Optimize the Polymer Discharge of Carbon Fiber Reinforced PEEK - Moritzer, Elmar; Wächter, Julian; Elsner, Christian Lennart (Macromolecular Symposia)

Stainless Steel Parts Produced by Fused Deposition Modeling and a Sintering Process Compared to Components Manufactured in Selective Laser Melting - Moritzer, Elmar; Schumacher, Christian (Macromolecular Symposia)

Modeling of Stiffness Anisotropy in Simulation of Self-Piercing Riveted Components - Otroshi, Mortaza; Meschut, Gerson; Bielak, Christian Roman; Masendorf, Lukas; Esderts, Alfons (Key Engineering Materials)

Investigation and Realization of Watertight FDM Structures Made of Ultem 9085 in Pressurized Systems - Moritzer, Elmar; Elsner, Christian Lennart; Wächter, Julian; Knoop, Frederick (79th Annual Technical Conference of the Society of Plastics Engineers (ANTEC))

Influence of material degradation on weld seam quality in hot gas butt welding of polyamides - Bialaschik, Max; Schöppner, Volker; Albrecht, Mirko; Gehde, Michael (Welding in the World)
The joining of plastics is required because component geometries are severely restricted in conventional manufacturing processes such as injection molding or extrusion. In addition to established processes such as hot plate welding, infrared welding, or vibration welding, hot gas butt welding is becoming more and more important industrially due to its advantages. The main benefits are the contactless heating process, the suitability for glass fiber reinforced, and high-temperature plastics as well as complex component geometries. However, various degradation phenomena can occur during the heating process used for economic reasons, due to the presence of oxygen in the air and to the high gas temperatures. In addition, the current patent situation suggests that welding with an oxidizing gas is not permissible depending on the material. On the other hand, however, there is experience from extrusion welding, with which long-term resistant weld seams can be produced using air. Investigations have shown that the same weld seam properties can be achieved with polypropylene using either air or nitrogen as the process gas. Experimental investigations have now been carried out on the suitability of different gases with regard to the weld seam quality when welding polyamides, which are generally regarded as more prone to oxidation. The results show that weld strengths are higher when nitrogen is used as process gas. However, equal weld strengths can be achieved with air and nitrogen when the material contains heat stabilizers.

Investigation of Metal‐Polymer Composites Manufactured by Fused Deposition Modeling with Regard to Process Parameters - Moritzer, Elmar; Elsner, Christian Lennart; Schumacher, Christian (Polymer Composites)

Fügen und Trennen von Kfz-Karosseriestrukturen in Leichtbauweise - Wibbeke, Tim Michael; Bartley, Auerélie; Chudalla, Nick; Meschut, Gerson (Fahrzeug + Karosserie und kfz-betrieb (Hrsg,); Tagungsband zu den Würzburger Karosserie- und Schadenstagen 22./23. Oktober 2021)

Clinching of Thermoplastic Composites and Metals—A Comparison of Three Novel Joining Technologies - Gröger, Benjamin; Troschitz, Juliane; Vorderbrüggen, Julian; Vogel, Christian; Kupfer, Robert; Meschut, Gerson; Gude, Maik (Materials)

Computed tomography investigation of the material structure in clinch joints in aluminium fibre-reinforced thermoplastic sheets - Gröger, Benjamin; Köhler, Daniel; Vorderbrüggen, Julian; Troschitz, Juliane; Kupfer, Robert; Meschut, Gerson; Gude, Maik (Production Engineering)
Abstract Recent developments in automotive and aircraft industry towards a multi-material design pose challenges for modern joining technologies due to different mechanical properties and material compositions of various materials such as composites and metals. Therefore, mechanical joining technologies like clinching are in the focus of current research activities. For multi-material joints of metals and thermoplastic composites thermally assisted clinching processes with advanced tool concepts are well developed. The material-specific properties of fibre-reinforced thermoplastics have a significant influence on the joining process and the resulting material structure in the joining zone. For this reason, it is important to investigate these influences in detail and to understand the phenomena occurring during the joining process. Additionally, this provides the basis for a validation of a numerical simulation of such joining processes. In this paper, the material structure in a joint resulting from a thermally assisted clinching process is investigated. The joining partners are an aluminium sheet and a thermoplastic composite (organo sheet). Using computed tomography enables a three-dimensional investigation that allows a detailed analysis of the phenomena in different joining stages and in the material structure of the finished joint. Consequently, this study provides a more detailed understanding of the material behavior of thermoplastic composites during thermally assisted clinching.

Measurement and Analysis of Residual Stresses and Warpage in Fiber Reinforced Plastic and Hybrid Components - Wu, Tao; Tinkloh, Steffen Rainer; Tröster, Thomas; Zinn, Wolfgang; Niendorf, Thomas (Metals)
Glass/carbon fiber reinforced plastic (GFRP/CFRP) and hybrid components have attracted increasing attention in lightweight applications. However, residual stresses induced in the manufacturing process of these components can result in warpage and, eventually, negatively affect the mechanical performance of the composite structures. In the present work, GFRP, CFRP, GFRP/steel and CFRP/steel hybrid components were manufactured through the prepreg-press-technology always employing the same process parameters. The residual stresses of these components were measured through the hole drilling method (HDM), based on an adequate formalism to evaluate the residual stresses for orthotropic materials including the calculation of the calibration coefficients via finite element analysis (FEA). In FEA, the real material lay-up and mechanical properties of the samples were considered. The warpage induced by residual stresses was measured after the samples were removed from the tool. The measured residual stresses and warpage of four different types of samples were compared and results were analyzed in depth. The results obtained can be extended to other hybrid materials and even could be used for designing multi-stable laminates for application in adaptive structures. Moreover, the effects of the drilling process parameters of HDM, e.g., the drilling speed, the drilling increment and the zero-depth setting, on the resulting residual stresses of GFRP were investigated. The reliability of residual stress measurements in GFRP using HDM was validated through mechanical bending tests. The conclusions concerning the choice of optimal drilling parameters for GFRP could be directly applied for other types of samples considered in the present work.

The Effect of Fiber Waviness on the Residual Stress State and Its Prediction by the Hole Drilling Method in Fiber Metal Laminates: A Global-Local Finite Element Analysis - Tinkloh, Steffen Rainer; Wu, Tao; Tröster, Thomas; Niendorf, Thomas (Metals)

On the reliability of residual stress measurements in unidirectional carbon fibre reinforced epoxy composites - Magnier, A.; Wu, T.; Tinkloh, Steffen Rainer; Tröster, Thomas; Scholtes, B.; Niendorf, T. (Polymer Testing)

Entwurf netzfreundlicher Synchrongleichrichter mit integriertem Synchronwandler - Henkenius, Carsten

Measurement procedure for acoustic absorption and bulk viscosity of liquids - Claes, Leander; Chatwell, René Spencer; Baumhögger, Elmar; Hetkämper, Tim; Zeipert, Henning; Vrabec, Jadran; Henning, Bernd (Measurement)

Towards a Decision Support System for Cross-Sectoral Energy Distribution Network Planning - Kirchhoff, Jonas; Burmeister, Sascha Christian; Weskamp, Christoph; Engels, Gregor (Energy Informatics and Electro Mobility ICT)
Requirements for energy distribution networks are changing fast due to the growing share of renewable energy, increasing electrification, and novel consumer and asset technologies. Since uncertainties about future developments increase planning difficulty, flexibility potentials such as synergies between the electricity, gas, heat, and transport sector often remain unused. In this paper, we therefore present a novel module-based concept for a decision support system that helps distribution network planners to identify cross-sectoral synergies and to select optimal network assets such as transformers, cables, pipes, energy storage systems or energy conversion technology. The concept enables long-term transformation plans and supports distribution network planners in designing reliable, sustainable and cost-efficient distribution networks for future demands.

Revolten in Gelb und Grün. In 'Rosa und Hannah. Das Blatt wenden' inspiriert Joke J. Hermsen für Krisenzeiten - Lammer, Christina

Designing of thermosetting plastic components for direct screwing - Auslegung von Duroplastbauteilen zur Direktverschraubung - Moritzer, Elmar; Hillemeyer, Johannes; Kramer, M.; Hopmann, C. (Joining Plastics)

Characterization of wood-filled thermoplastic polyurethanes for the injection molding process - Moritzer, Elmar; Richters, Maximilian (Journal of Applied Polymer Science)

Entwicklung der Spritzniettechnik als werkstoffgerechtes Fügeverfahren für hybride Strukturen - Moritzer, Elmar; Krassmann, Dimitri; Brikmann, Johannes (11. Fügetechnisches Gemeinschaftskolloquium)

Er kommt auf die Korngröße an, Mikrogranulat verbessert die Verteilung feindisperser Füllstoffe in der Direktcompoundierung - Moritzer, Elmar; Jilg, J.; Rücker, Tobias (Kunststoffe)

Eine runde Sache - Schöppner, Volker; Martens, Jan Hendrik (Kunststoffe)

Influence of Fiber Content on the Fiber Dust Formation During Shredding for Mechanical Recycling of Different Glass and Carbon Fiber Reinforced Thermoplastics - Hopp, Matthias; Tölle, Lisa (36th International Conference of Polymer Processing Society (PPS))

Fügeelement angespritzt - Einfluss auf die Verbundfestigkeit zwischen Organoblech und Schraubblindniet untersucht - Moritzer, Elmar; Hillemeyer, Johannes; Lotzin, R. (Kunststoffe)

Effect of Isocyanate Absorption on the Mechanical Properties of Silicone Elastomers in Polyurethane Vacuum Casting - Moritzer, Elmar; Wortmann, M.; Krieger, P.; Hüsgen, B.; Frese, N. (ACS Omega)

INVESTIGATION OF THE PROCESSABILITY OF DIFFERENT HIGHPERFORMANCE MATERIALS IN THE FDM PROCESS WITH REGARD TO THE SHRINKAGE BEHAVIOR - Moritzer, Elmar; Wächter, Julian; Fuhrmann, C. (23rd International Conference Materials)

Lebensdauer vorhersagen? - Schöppner, Volker; Gevers, Karina (K-Zeitung)

Kühlen mit dem Wärmerohr - Moritzer, Elmar (Kunststoffe)

Material Degradation of Polypropylene on the Co-Rotating Twin Screw Extruder - Schöppner, Volker; Altepeter, Matthias; Wanke, Sven (36th International Conference of the Polymer Processing Society (PPS))

Schriftstellerische Inszenierungspraktiken und autofiktionale Schreibreflexionen im Weblog Turmsegler von Benjamin Stein - Willeke, Stephanie (Schreiben, Text, Autorschaft II. Zur Narration und Störung von Lebens- und Schreibprozessen)

Untersuchung der Faserlängenabnahme von kurz- und langglasfaserverstärk-ten Thermoplasten im Spritzgießprozess - Moritzer, Elmar; Bürenhaus, Franziska Isabelle (27. Techomer - Fachtagung über Verarbeitung und Anwendung von Polymeren)

Auf der Grenze zwischen Fakt und Fiktion. Fake News in der Polit-Serie The Good Fight - Willeke, Stephanie (Prekäre Fakten, umstrittene Fiktionen. Fake News, Verschwörungstheorien und ihre kulturelle Aushandlung (Philologie im Netz Beiheft 25/2021))

Molding on a Joining Element - Study of the Factors Influencing the Strength of the Bond between a Thermoplastic Composite and a Screw-in Blind Rivet - Moritzer, Elmar; Hillemeyer, Johannes; Lotzin, R. (Kunststoffe International)

Reduzierung der Faserstaubentstehung beim mechanischen Recycling - Zerkleinern von carbonfaserverstärkten Polycarbonaten mit unterschiedlichen Verstärkungsformen - Hopp, Matthias; Tölle, Lisa; Hoemann, Theresa (Gummi Fasern Kunststoffe)

Silicone Mold Accuracy in Polyurethane Vacuum Casting - Moritzer, Elmar; Wortmann, M.; Frese, N.; Brinkmann, J.; Ehrmann, A.; Hüsgen, B. (Macromolecular Symposia)

Viskoelastische Materialmodellierung in Strömungssimulationen - Schöppner, Volker; Kleinschmidt, Dennis (27. Techomer - Fachtagung über Verarbeitung und Anwendung von Polymeren)

Warmgasstumpfschweißen - Einfluss des Werkzeugdesigns und des verwendeten Prozessgases auf das Erwärm- und Schweißverhalten - Schöppner, Volker; Albrecht, M.; Gehde, M.; Bialaschik, Max Oliver (Technomer)

Vorteilhaftes Prozessverhalten von Wave-Schnecken in der Einschneckenextrusion - Schöppner, Volker; Dörner, M.; Schall, Christoph Wilhelm Theodor (Technomer 2021)

Warmgasstumpfschweißen von Kunststoffen - Schöppner, Volker; Bialaschik, Max Oliver; Albrecht, M.; Gehde, M. (Joining Plastics)

„Transkulturelle Wahrnehmungsräume in der Theaterdidaktik. Die Theaterarbeit von Nuran David Calis“ - Böker, Ines (Drama und Theater der Gegenwart. Literarisches Lernen und ästhetische Bildung zwischen Textanalyse und Aufführungsrezeption (Beiträge zur Didaktik der deutschsprachigen Gegenwartsliteratur))

Investigation of Fiber Orientation and its Influence on Fiber Length Degradation in Simple Shear Flow for Glass Fiber Reinforced Polypropylene - Moritzer, Elmar; Bürenhaus, Franziska Isabelle (36th International Conference of the Polymer Processing Society (PPS))

Classifying the Ideational Impact of Information Systems Review Articles: A Content-Enriched Deep Learning Approach - Prester, Julian; Wagner, Gerit; Schryen, Guido; Hassan, Nik Rushdi (Decision Support Systems)
Ideational impact refers to the uptake of a paper's ideas and concepts by subsequent research. It is defined in stark contrast to total citation impact, a measure predominantly used in research evaluation that assumes that all citations are equal. Understanding ideational impact is critical for evaluating research impact and understanding how scientific disciplines build a cumulative tradition. Research has only recently developed automated citation classification techniques to distinguish between different types of citations and generally does not emphasize the conceptual content of the citations and its ideational impact. To address this problem, we develop Deep Content-enriched Ideational Impact Classification (Deep-CENIC) as the first automated approach for ideational impact classification to support researchers' literature search practices. We evaluate Deep-CENIC on 1,256 papers citing 24 information systems review articles from the IT business value domain. We show that Deep-CENIC significantly outperforms state-of-the-art benchmark models. We contribute to information systems research by operationalizing the concept of ideational impact, designing a recommender system for academic papers based on deep learning techniques, and empirically exploring the ideational impact of the IT business value domain.
Keywords: Ideational impact; citation classification; academic recommender systems; natural language processing; deep learning; cumulative tradition

Which Factors Affect the Scientific Impact of Review Papers in IS Research? A Scientometric Study - Wagner, Gerit; Prester, Julian; Roche, Maria; Schryen, Guido; Benlian, Alexander; Paré, Guy; Templier, Mathieu (Information & Management)
Review papers are essential for knowledge development in IS. While some are cited twice a day, others accumulate single digit citations over a decade. The magnitude of these differences prompts us to analyze what distinguishes those reviews that have proven to be integral to scientific progress from those that might be considered less impactful. Our results highlight differences between reviews aimed at describing, understanding, explaining, and theory testing. Beyond the control variables, they demonstrate the importance of methodological transparency and the development of research agendas. These insights inform all stakeholders involved in the development and publication of review papers.
Keywords: Literature review; review papers; scientometric; scientific impact; citation analysis

Study on Sensitivity of Electric Bus Systems under Simultaneous Optimization of Charging Infrastructure and Vehicle Schedules - Stumpe, Miriam; Rößler, David; Schryen, Guido; Kliewer, Natalia (EURO Journal on Transportation and Logistics)

Exploring the Scientific Impact of Information Systems Design Science Research - Wagner, Gerit; Prester, Julian; Schryen, Guido (Communications of the Association for Information Systems)

Sprachbildung in der Grundschule - Altun, Tülay; Handt, Claudia; Hinrichs, Beatrix; Hoffacker, Anna; Niederhaus, Constanze; Weis, Ingrid

Schreibberatung im Kontext beruflicher Bildung und ihre Auswirkung auf Emotionen beim Schreiben - Dohmann, Olga; Drumm, Sandra; Niederhaus, Constanze (Zur sprachlichen und gesellschaftlichen Integration neu zugewanderter Menschen. Eine Bilanz. Materialien Deutsch als Zweit- und Fremdsprache 105)

Der besondere Moment - Ergebnisse aus der Evaluation der Projekte „Sprachförderung PLUS“ im Netzwerk „Stark durch Diversität“ - Peuschel, Kristina; Petersen, Inger; Reble, Raja; Haberzettl, Stefanie; Berkel-Otto, Lisa; Niederhaus, Constanze; Steinmetz, Sandra; Rojahn, Pia; Sondershaus, Eva (Theorie-Praxis-Verzahnung in der Lehrkräftebildung Ergebnisse aus dem Netzwerk „Stark durch Diversität“)